(untitled) (Bioscience Journal, 2021)
This study was performed to evaluate the effectiveness of Echinacea purpurea (E.P.) on azathioprine (AZA)-induced immune deficiency in albino rats. Thirty six male albino rats were divided into six equal groups. The first group served as normal control, the second and third groups were treated with two doses of AZA (3 and 5mg/kg/b.w/day IP), respectively for six weeks. The fourth group was treated with 50 mg kg/b.wt/day of Echinacea. The fifth and sixth groups were treated with3 and 5 mg AZAm respectively followed by50 mg E.P. administration. At the end of the experimental period, both doses of AZA revealed a significant reduction in total body and spleen weights, increase in tissue total protein with a significant increase in serum total protein and albumin, a marked decrease in the number of WBCS associated with a decrease in the number of lymphocytes, a significant decrease in serum total anti-oxidant capacity. Also,concentration of immunoglobulins (IgG and IgM) and interleukins (IL4 &IL6) showed a significant increase, while the level of IL10 decreased significantly in splenic tissue. The dose of AZA (5 mg /kg b.wt.) only resulted in a highly significant increase in serum level of T3 and T4. However, treatment with Echinacea purpurea extract had a significant influence on immune deficiency induced by azathioprine. These findings demonstrated that E.P. extract is a promising immunomodulatory agent with a potent therapeutic value in stimulating the immune response.